2020
DOI: 10.3389/fimmu.2020.567856
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Hyper IgM Syndrome Identified by Whole Genome Sequencing in a Young Syrian Man Presenting With Atypical, Severe and Recurrent Mucosal Leishmaniasis

Abstract: A previously healthy 19-year-old Syrian man presented with atypical and severe mucosal leishmaniasis caused by Leishmania tropica. During a 2-year period, he had three severe relapses despite various treatment strategies, including liposomal amphotericin B and Miltefosine. Because of the unusual clinical presentation, potential underlying immunodeficiency was investigated. Normal T and NK cell counts were found. The B cell count was slightly elevated at 0.7 × 10 9 cells/L (0.09 × 10 9 to 0.57 × 10 9 cells/L), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Since the first description of visceral leishmaniasis in XHIGM syndrome by Martìn et al. in 1996, only a few cases have been reported so far in the literature ( 25 27 ). CD40L deficiency’s main feature is hypogammaglobulinemia, caused by the central role of the CD40–CD40L interaction in the class-switch recombination in B cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first description of visceral leishmaniasis in XHIGM syndrome by Martìn et al. in 1996, only a few cases have been reported so far in the literature ( 25 27 ). CD40L deficiency’s main feature is hypogammaglobulinemia, caused by the central role of the CD40–CD40L interaction in the class-switch recombination in B cells.…”
Section: Discussionmentioning
confidence: 99%
“…flere og svaerere kutane elementer, udvikling af mukokutan sygdom [7] som udvikling af visceral leishmaniasis.…”
Section: Ugeskrift For Laeger Ugeskrift For Laegerunclassified
“…Since the first description of visceral leishmaniasis in XHIGM syndrome by Martìn et al in 1996, only a few cases have been reported so far in the literature (25)(26)(27). CD40L deficiency's main feature is hypogammaglobulinemia, caused by the central role of the CD40-CD40L interaction in the class-switch recombination in B cells.…”
Section: Discussionmentioning
confidence: 99%